2000
DOI: 10.1590/s0004-282x2000000200011
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da coerência do eletrencefalograma para a banda de frequência alfa em indivíduos adultos normais e com provável demência do tipo Alzheimer

Abstract: RESUMO -Estudamos a coerência inter-hemisférica do espectro do eletrencefalograma (EEG) obtido pela transformada rápida de Fourier, da região occipital do escalpo (eletrodos O1 e O2) para a banda de frequência alfa (alfa 1 -8,0 a 10,0 Hz e alfa 2 -10,1 a 12,5 Hz) em indivíduos normais maiores de 50 anos e pacientes com diagnóstico provável de demência do tipo Alzheimer (DTA), no intuíto de observar se há diferenças entre estes parâmetros que contribuam com o diagnóstico desta enfermidade. Encontramos diminuiçã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 18 publications
1
13
0
4
Order By: Relevance
“…Concerning the inter-hemispheric coherence value found in the present study for each age bracket of the sample, no significant differences were observed between the 20-29 year, 30-39 year, and 40-49 year age groups. For the 20-50 year age group, EEG spectral characteristics tend to change little, in contrast to both younger (under 10 years) and elderly (over 60 years) groups, according to previous studies in our setting [17][18] . Marozi et al 19 , in an evolutive study, found increased coherence in the frontal region across all bands, except beta, in a population of 46 students followed for 3 years.…”
Section: Discussionsupporting
confidence: 80%
“…Concerning the inter-hemispheric coherence value found in the present study for each age bracket of the sample, no significant differences were observed between the 20-29 year, 30-39 year, and 40-49 year age groups. For the 20-50 year age group, EEG spectral characteristics tend to change little, in contrast to both younger (under 10 years) and elderly (over 60 years) groups, according to previous studies in our setting [17][18] . Marozi et al 19 , in an evolutive study, found increased coherence in the frontal region across all bands, except beta, in a population of 46 students followed for 3 years.…”
Section: Discussionsupporting
confidence: 80%
“…In alpha (1-C), main effects of condition [F (2,267) = 7.537; p=0.001], moment [F (2,267) =4.825; p=0.009], and electrode site [F (2,267) =21.345; p=0.000] were found. No interactions were observed.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, the EEG has been widely employed in the assessment of electrophysiological changes induced by distinct medications. Its sensibility in detecting alterations produced by a specific substance may be enhanced by methods of quantitative analyses (qEEG) 2,3 . Quantitative electroencephalography has become, throughout the years, a tool of great clinical utility in evaluating the effects of medications, predicting medication response, and in assessment of cognitive changes produced by such psychoactive substances.…”
Section: Palavras-chave: Bromazepam Eegqmentioning
confidence: 99%
“…In this context, electroencephalography (EEG) has been used to monitor the effects of distinct medications on brain dynamics since cortical activity is responsive to the unique characteristics of psychoactive substances (Saletu et al 2002). The EEG sensibility in identifying changes produced by a specific substance may be improved by methods of quantitative analyses (qEEG) (Anghinah et al 2000, Veiga et al 2003. Once drugs have specific effects on wave morphology, changes in qEEG variables can be used to investigate Correspondence to: Isabel Sampaio E-mail: belsampaio@gmail.com mechanisms of drug action as well as to monitor and possibly predict efficacy (Fink 1978).…”
Section: Introductionmentioning
confidence: 99%